Analysis of the Level of Understanding of the Concept of the Isoline Method of Linear Program Material Based on APOS Theory in terms of Learning Interest - Iesyah Rodliyah; Dwi Juniati; Siti Khabibah (Jurnal Gantang, 2022)
One of the methods that can be used to find solutions to linear programming models is the Graphical Method. Graphical methods are divided into the isoline method and the extreme point method. Based on initial observations and interviews, it was found that around 54% of students still needed help understanding the isoline method material in solving linear programs, especially when given real problems related to everyday life. In addition, students' learning interest in linear programming courses also varies. So the purpose of research in this article is to describe the level of understanding of students who have high, medium, and low learning interest in linear programming material, precisely the isoline method material, in determining the optimum solution. The method in this study is a qualitative method with a sampling technique using purposive sampling. Data collection was carried out using a questionnaire method for data on student learning interests and semi-structured test and interview methods to describe the level of student understanding based on APOS theory. The instruments in this study were questionnaires, written tests, and interview guidelines. Checking the validity of the data in this study used time triangulation. The collected data was analyzed using descriptive qualitative analysis. The results of the research show that: (1) subjects with high learning interest are at the level of schematic understanding; (2) subjects with interest in learning are at the level of understanding objects; and (3) subjects with low interest in learning are at the level of understanding of Action.